MANAGEMENT OF TRANSBOUNDARY RIVERS IN INTERNATIONAL LAW: THE CASE OF THE AMU DARYA AND SYR DARYA - Xudoyberdiyev Otabek Zafar o'g'li (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation: This article examines the legal and institutional frameworks for managing transboundary rivers under international law, with a specific focus on the Amu Darya and Syr Darya rivers in Central Asia. These rivers, shared by multiple countries, are essential sources of freshwater for agriculture, energy production, and domestic use. The paper analyzes key international legal principles such as equitable and reasonable utilization, the obligation not to cause significant harm, and the duty to cooperate. It also explores regional agreements, including those from the post-Soviet period, and evaluates their effectiveness in resolving water allocation disputes. Special attention is given to the challenges of upstream-downstream dynamics and the potential of international legal mechanisms to foster sustainable and cooperative water governance in the region.